Recurrent non‐traumatic idiopathic chylothorax: a diagnostic dilemma with therapeutic challenge. Issue 7 (30th August 2020) - Vadala, Rohit; Talwar, Dhruv; Talwar, Deepak
Abstract: Chylothorax is an uncommon pleural effusion characterized by the presence of chyle in the pleural space. Malignancy, trauma, and infections such as tuberculosis and filariasis can result in chylothorax. The chyle is an odourless and white liquid; however, around 50% of chylothorax is not milky (serosanguineous) and 10% of chylothorax is idiopathic which can pose a diagnostic dilemma. We propose a systematic approach which includes pleural fluid triglycerides and cholesterol for all undiagnosed pleural effusion. The case highlights the diagnostic dilemma as well as therapeutic challenges. Abstract : This study highlights the recurrent non‐traumatic idiopathic chylothorax with proposed algorithmic approach to undiagnosed milky or turbid blood‐tinged pleural effusion.